2023
DOI: 10.1038/s41598-023-31511-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical exercise and smoking behavior among Chinese residents aged 16 years and older

Abstract: To explore the relationship between physical exercise and smoking behavior among Chinese residents aged 16 years and older. Analysis based on 29,466 validated cases in the 2018 China Family Panel Studies (CFPS 2018). The chi-square test and Mann–Whitney U test were used for comparative analysis between groups. Logistic regression analysis was used to explore the relationship between physical exercise and smoking behavior. Gender and birth cohort differences in the relationship between physical exercise and smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Moreover, a higher physical activity was characteristic of alcohol consumers with a higher level of education, low TV viewing, and non-tobacco smokers [38]. Previous studies also showed that there is a negative correlation between cigarette smoking and the quality of physical activity [39], moreover, physical inactivity was associated with smoking in old adults [40,41]. Bilateral relationships between these components were not confirmed in a more comprehensive cluster analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, a higher physical activity was characteristic of alcohol consumers with a higher level of education, low TV viewing, and non-tobacco smokers [38]. Previous studies also showed that there is a negative correlation between cigarette smoking and the quality of physical activity [39], moreover, physical inactivity was associated with smoking in old adults [40,41]. Bilateral relationships between these components were not confirmed in a more comprehensive cluster analysis.…”
Section: Discussionmentioning
confidence: 92%